A rare case of a native aortic valve fungal endocarditis in a young woman - Piątek, Łukasz; Piątek, Karolina; Kurzawski, Jacek; Domagała, Szymon; Turek, Łukasz; Starzyk, Zbigniew; Pietrzyk, Edward (Medical Studies/Studia Medyczne, 2022)
We present a rare case of a native aortic valve fungal endocarditis in a young obese woman. Our patient had undergone a bariatric surgery followed by numerous local complications associated with further surgical procedures and multiple antibiotic treatments. Six months later, she was admitted to our centre with signs of septicaemia. In echocardiography a massive tumour on the aortic valve was revealed. An urgent cardiosurgery operation was performed – the tumour was resected, and an artificial valve was implanted. Microbiological analysis of the tumour and blood samples confirmed fungal infection (Candida albicans). Intensive antifungal therapy was continued for 4 weeks. During the hospitalization serious embolic complications appeared. Finally, the patient responded well to the implemented treatment and was discharged in a good clinical condition. Our case presents an exceptionally rare form of cardiac infection, unexpected in immunocompetent patients. We associate this condition with an unfavourable course of the previous bariatric therapies.